2009
DOI: 10.1007/s11244-009-9284-3
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Nitrogen Containing Carbon Nanotubes in Base Catalyzed Knoevenagel Condensation

Abstract: The catalytic activity of Nitrogen containing Carbon Nanotubes (NCNT), grown from acetonitrile or pyridine over supported Fe-, Co or Ni catalysts at various conditions, were tested for the base catalyzed Knoevenagel condensation of benzaldehyde and ethylcyanoacetate. All NCNT displayed activity for the reaction with initial turn over frequencies between 9 9 10 -3 and 5 9 10 -2 s -1 which is comparable with to those of activated basic carbons and a rehydrated hydrotalcite. Furthermore, the initial activity per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
0
26
0
2
Order By: Relevance
“…The activity was, in this case, related to the amount of pyridinic nitrogen incorporated into the structure [713], while competitive adsorption of reactant and product is responsible for the activity decay [714]. Basic nature of MWNCNTs was also pointed as crucial for their use as catalysts for wet air oxidation of oxalic acid, while catalytic activity was found to decay during the catalytic process due to the loss of the basic character [385].…”
Section: Catalysis By 1-d Ncnss and Their Compositesmentioning
confidence: 92%
See 1 more Smart Citation
“…The activity was, in this case, related to the amount of pyridinic nitrogen incorporated into the structure [713], while competitive adsorption of reactant and product is responsible for the activity decay [714]. Basic nature of MWNCNTs was also pointed as crucial for their use as catalysts for wet air oxidation of oxalic acid, while catalytic activity was found to decay during the catalytic process due to the loss of the basic character [385].…”
Section: Catalysis By 1-d Ncnss and Their Compositesmentioning
confidence: 92%
“…Base properties of NCNTs enabled their use as a solid base catalyst for Knoevenagel condensation [713,714]. The activity was, in this case, related to the amount of pyridinic nitrogen incorporated into the structure [713], while competitive adsorption of reactant and product is responsible for the activity decay [714].…”
Section: Catalysis By 1-d Ncnss and Their Compositesmentioning
confidence: 97%
“…Nitrogen doping or amine grafting can enhance the basic strength of carbon materials. Bitter and co‐workers showed that nitrogen‐containing CNTs are effective for the Knoevenagel condensation of ethyl α‐cyanoacetate with benzaldehyde (Scheme ): an initial activity of 14 mmol g cat −1 h −1 was obtained over NCNTs . The activity was determined by the concentration of pyridinic nitrogen atoms, but both O and N heteroatoms were needed for the reaction, since a maximum activity was obtained at a surface N/O ratio of 0.8–1.0 .…”
Section: Typical Liquid‐phase Reactions Catalyzed By Carbonmentioning
confidence: 99%
“…As shown in [76][77][78], an aqueous suspension of N-CNTs has pH 8-9 and there exists a correlation between the number of basic sites and nitrogen content in the pyridine-like state [78,79]. The presence of pyridine-like nitrogen on the carbon surface opens interesting routes for the development of advanced bifunctional materials with different types of surface sites.…”
Section: Surface Properties Of N-cnmsmentioning
confidence: 99%
“…And finally, activity of N-CNTs was investigated in the acid-base catalysis using the Knoevenagel reaction [76,77]. CNTs were shown to be inactive in this reaction, while in the case of N-CNTs a direct dependence of catalytic activity on the concentration of pyridinelike nitrogen was found, Fig.…”
Section: N-cnms As the Catalystsmentioning
confidence: 99%